Cannabidiol Increases Seizure Resistance and Improves Behavior in an Scn8a Mouse Model - Shapiro, Lindsey; Escayg, Andrew; Wong, Jennifer C. (Frontiers in Pharmacology, 2022)
Voltage-gated sodium channel (VGSC) genes are an important family of human epilepsy genes. De novo missense mutations in SCN8A (encoding Nav1.6) are associated with a spectrum of clinical presentation, including multiple seizure types, movement disorders, intellectual disability, and behavioral abnormalities such as autism. Patients with SCN8A mutations are often treated with multiple antiepileptic drugs, the most common being sodium channel blockers. Cannabidiol (CBD) has been included as a component of treatment regimens for some SCN8A patients; however, to date, there are no clinical trials that have evaluated the therapeutic potential of CBD in patients with SCN8A mutations. In the current manuscript, we demonstrated a dose-dependent increase in seizure resistance following CBD treatment in mice expressing the human SCN8A mutation R1620L (RL/+). We also found that CBD treatment improved social behavior and reduced hyperactivity in the RL/+ mutants. Our findings suggest that CBD may be beneficial in patients with SCN8A-associated disease.